2022
DOI: 10.1111/cen3.12731
|View full text |Cite
|
Sign up to set email alerts
|

Japan MG registry: Chronological surveys over 10 years

Abstract: The primary purpose of the Japanese myasthenia gravis registry (JAMG-R) has been to research and promote high-quality medical care for MG patients in Japan. We reviewed the findings of surveys performed by JAMG-R over an ~10-y period. The first goal for favorable quality of life (QOL) is a status of minimal manifestations (MM) or better with an oral prednisolone (PSL) dose of 5 mg/d or less (MM-5 mg).Early and aggressive use of nonoral fast-acting treatment together with low-dose oral PSL (the "EFT strategy") … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Proportion of patients with LOMG receiving EFT was higher (despite the severity being milder) compared with EOMG in unmatched patients, which may reflect that treatment with EFT was preferred to avoid the risk of high-dose and long-term PSL use in elderly patients. In the current study, 45.4% of the patients with generalised MG received EFT and EFT was performed in 39% of patients in the overall JAMG-R survey, which included both patients with ocular and generalised MG,3 indicating that EFT is gradually becoming a common treatment for MG. As previously reported,11 12 our study confirms that MM and MM5mg are achieved more frequently and earlier when EFT is administered. The achievement rate of MM5mg increased with time until around 5 years after initiation of immunotherapy, after which it almost plateaued; MM5mg was achieved in 65% of the EFT group and 41% of the non-EFT group during the first 5 years, and the frequency of receiving moderate-to-high-dose PSL throughout the course was significantly lower in EFT group than the non-EFT group.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Proportion of patients with LOMG receiving EFT was higher (despite the severity being milder) compared with EOMG in unmatched patients, which may reflect that treatment with EFT was preferred to avoid the risk of high-dose and long-term PSL use in elderly patients. In the current study, 45.4% of the patients with generalised MG received EFT and EFT was performed in 39% of patients in the overall JAMG-R survey, which included both patients with ocular and generalised MG,3 indicating that EFT is gradually becoming a common treatment for MG. As previously reported,11 12 our study confirms that MM and MM5mg are achieved more frequently and earlier when EFT is administered. The achievement rate of MM5mg increased with time until around 5 years after initiation of immunotherapy, after which it almost plateaued; MM5mg was achieved in 65% of the EFT group and 41% of the non-EFT group during the first 5 years, and the frequency of receiving moderate-to-high-dose PSL throughout the course was significantly lower in EFT group than the non-EFT group.…”
Section: Discussionmentioning
confidence: 69%
“…Our study group consists of 20 Japanese institutions; of which, 13 participated in the JAMG-R study in 2021 (online supplemental table 1). 3 We diagnosed MG based on characteristic clinical features of MG and positivity for AChR/MuSK antibodies and/or neuromuscular junction disorder tests (eyelid easy fatigability test, ice pack test, edrophonium test, repetitive nerve stimulation test and/or jitter increase on single-fibre electromyography test). We included consecutive patients with MG who visited JAMG-R sites between April and October 2021, evaluated currents status (severity, subtype and treatment), and retrospectively collected clinical data of onset age, disease duration, sex, past treatment regimens, disease status at its worst and duration from start of treatment to first achievement of MM and MM5mg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…compared the time to first achieve MM‐5 mg from 6 to 120 months after starting immunotherapy between EFT and non‐EFT patients, and found that achievement of MM‐5 mg was more frequent and earlier in the EFT group 30 . The recent JAMG‐R data showed that approximately 40% of all patients with MG received EFT, and those experiencing MM‐5 mg increased from 53% in 2015 to 65% in 2021 10 . Thus, EFT has been proved to be an exceedingly powerful tool to achieve the treatment goal.…”
Section: Early Fast‐acting Treatment For Mgmentioning
confidence: 99%
“…30 The recent JAMG-R data showed that approximately 40% of all patients with MG received EFT, and those experiencing MM-5 mg increased from 53% in 2015 to 65% in 2021. 10 Thus, EFT has been proved to be an exceedingly powerful tool to achieve the treatment goal.…”
Section: Recommendationsmentioning
confidence: 99%